Decreased Immunity to Varicella Zoster Virus in Giant Cell Arteritis - Rondaan, Christien; van der Geest, Kornelis S. M.; Eelsing, Elisabeth; Boots, Annemieke M. H.; Bos, Nicolaas A.; Westra, Johanna; Brouwer, Elisabeth (Frontiers in Immunology, 2017)
Introduction. Herpes zoster, which can have a major impact on quality of life, results from reactivation of a latent varicella-zoster virus (VZV) infection. We hypothesized that giant cell arteritis (GCA) patients are at increased risk of herpes zoster because of treatment with high-dose glucocorticoids and advanced age. Aim of the study therefore was to determine cell-mediated and humoral immunity to VZV in patients with GCA, patients with closely related disease polymyalgia rheumatica (PMR; treated with lower doses of glucocorticoids) and healthy controls. Methods. Cell-mediated immunity to VZV was determined by performing interferon-γ (IFNγ) enzyme-linked immunospot (ELISpot) and intracellular cytokine flow cytometry measurements in 11 GCA and 15 PMR patients, and in 26 age/sex-matched healthy controls. Immunoglobulin G antibodies to VZV glycoprotein (VZV-IgG) were measured in serum samples of 35 GCA and 26 PMR patients at different times of follow-up, and in 58 age and sex matched healthy controls by an enzyme-linked immunosorbent assay (ELISA). Results. The number of VZV-specific IFNγ spot-forming cells was significantly lower in GCA patients on treatment, than in age-matched healthy controls (p=0.029), but was not different in PMR patients on treatment. Similar levels of VZV-IgG were found in GCA and PMR patients at baseline, compared to healthy controls. Conclusion. The finding of a decreased cell-mediated immunity to VZV, known to be of great importance in defense to the virus, indicates an increased herpes zoster risk in GCA patients compared to an already at-risk elderly population. Herpes zoster vaccination is therefore of special importance in GCA patients, and would ideally be administered at time of diagnosis. Interestingly, as VZV was suggested to be the trigger in GCA pathogenesis, similar levels of VZV-IgG were found in GCA patients at time of diagnosis and age matched healthy controls, indicating that GCA patients did not experience herpes zoster substantially more often in the months preceding diagnosis than controls.